The influence of reinforcement on load carrying capacity and cracking of the reinforced concrete deep beam joint. (15th January 2016) - Kopańska, Anna; Nagrodzka-Godycka, Krystyna
Highlights: Experimental research of the spatial reinforced concrete deep beams is reported. Deep beams orthogonally reinforced and with additional bent up bars were analyzed. Deep beam systems composed with a cantilever deep beam loaded throughout the depth. The inclined reinforcement ensures the increase of the load carrying capacity. The diagonal reinforcement influenced also favorably on limitation of cracks width. Abstract: The paper presents the results of experimental research of the spatial reinforced concrete deep beam systems orthogonally reinforced and with additional inclined bars. Joint of the deep beams in this research was composed of the longitudinal deep beam with a cantilever suspended at the transversal deep beam. The cantilever deep beam was loaded throughout the depth and the transversal deep beam was loaded at the mid-span by longitudinal deep beam attached to it. Morphology of cracking and stresses in the reinforcing steel, as well as the load distribution in the cantilever deep beams using Strut-and-Tie model taking into account an effort of concrete compression strut and efficiency of softening coefficient are presented and discussed. In the paper, the effectiveness of the mixed reinforcement in both tested deep beam systems, as referred to the design recommendation proposed in the published papers is also verified. It is also demonstrated that the inclined reinforcement favorably influences the width of cracks in cantilever and transversal deep beams and ensures the increase of the load carrying capacity.